ANALISIS PENERAPAN SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN BARANG (STUDI KASUS PADA PT ARAZ INTI LINE) - Said, Muhammad Afiq Satrio; Kilay, Trisye Natalia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
Inventory management is a crucial aspect of any company that needs to be managed well. However, it has been discovered that at PT Araz Inti Line, only one employee is responsible for inventory entering and leaving the warehouse. This poses a risk of inventory discrepancies or loss. As a result, this research aims to analyze the implementation of the inventory receipt and expenditure information systems at PT Araz Inti Line. Qualitative data from primary sources such as interviews and observations and secondary sources such as documentation of inventory accounting information systems were used in conducting this research. The research methodology utilized descriptive data analysis techniques. The findings indicate that the receiving and releasing of goods at PT Araz Inti Line are not adequately implemented. There is a lack of proper segregation of duties for recording inventory in physical and rupiah terms. Additionally, essential documents such as goods receipt reports are found absent.